2014
DOI: 10.21608/jfds.2014.52749
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Aflatoxin M1 in Some Dairy Products in Local Market of Alexandria, Egypt: Attempts for Detoxification

Abstract: Aflatoxins are carcinogenic and toxic metabolites produced by a variety of molds. Aflatoxin M1 (AFM1) accumulates in animal livers and it is excreted in milk, which can be consumed by human. The present study was undertaken aiming at examining the dairy milk products for their any contamination of AFM1 in Alexandria local market, Egypt, as well as conducting trials for elimination of AFM1 contamination by using ozone gas and gamma radiation. Levels of AFM1 contamination (0.001 to 0.06) were ranged from in exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
1
1
1
Order By: Relevance
“…Findings related to Ras cheese were in agreement with Amer and Ibrahim [35] and Aiad and Abo Ei-Makarem [11] who found that the mean AFM 1 value in the examined Ras cheese was 56.048±6.29 ng/kg; while higher than Hosny et al [37], Ahmed et al [22], and Younis et al [38] who reported that the examined samples of Ras cheese were contaminated with AFM 1 with a mean value of 15 ng/kg. The results were lower than those cited by Nassib et al [39] and Abdel All et al [40].…”
Section: Prevalence Of Afm 1 In the Examined Samplessupporting
confidence: 90%
“…Findings related to Ras cheese were in agreement with Amer and Ibrahim [35] and Aiad and Abo Ei-Makarem [11] who found that the mean AFM 1 value in the examined Ras cheese was 56.048±6.29 ng/kg; while higher than Hosny et al [37], Ahmed et al [22], and Younis et al [38] who reported that the examined samples of Ras cheese were contaminated with AFM 1 with a mean value of 15 ng/kg. The results were lower than those cited by Nassib et al [39] and Abdel All et al [40].…”
Section: Prevalence Of Afm 1 In the Examined Samplessupporting
confidence: 90%
“…Of these samples, 5 (33.3%) exceeded the Egyptian regulation limit for AFM1 (0 ng/L) while only 2 (13.3%) samples exceeded the European Commission regulation (50 ng/L) ( Table 2). Lower findings were obtained by Aiad and Aboelmakarem [16] while higher result by Hosny et al [17]. The present study revealed the contamination of the examined samples with AFM1 in milk and dairy products thus posing a potential risk to human health.…”
Section: Resultscontrasting
confidence: 72%
“…All the positive samples exceeded the Egyption regulation limit, while, 2 (13.3%) samples exceeded the European Commission regulation (Tables 1, 2). Higher result was reported by Hosny et al [17]. In another investigations, AFM1 was detected in cheese with the values 64, 64.8, 78 and 80% [22][23][24][25].…”
Section: Resultsmentioning
confidence: 73%